2022
DOI: 10.1136/jcp-2021-208029
|View full text |Cite
|
Sign up to set email alerts
|

Homocystinuria diagnosis and management: it is not all classical

Abstract: Homocystinuria (HCU) refers to a group of inherited disorders of homocysteine metabolism associated with high blood homocysteine concentration, thromboembolic tendency and neurocognitive symptoms. The most common causes of a high blood homocysteine relate to underlying vitamin B12 or folate deficiency which must be excluded first. Thereafter, an inherited metabolic condition can be considered.The most prevalent inherited disorder of homocysteine metabolism is classical HCU caused by deficiency of the pyridoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…In addition, studies have shown that certain diseases such as neonatal defects, arteriovenous thrombosis, diabetes, stroke, Alzheimer’s, and Parkinson’s disease are also associated with abnormal Hcy metabolism [ 9 , 11 , 12 ]. Since the high concentrations of Hcy can induce the risk of various diseases, a variety of methods for the detection of Hcy have been developed clinically to facilitate clinical diagnosis and prevention [ 13 , 14 , 15 ]. The biomarkers of DM have been studied by metabolomics, which also involve the metabolites on Hcy metabolism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that certain diseases such as neonatal defects, arteriovenous thrombosis, diabetes, stroke, Alzheimer’s, and Parkinson’s disease are also associated with abnormal Hcy metabolism [ 9 , 11 , 12 ]. Since the high concentrations of Hcy can induce the risk of various diseases, a variety of methods for the detection of Hcy have been developed clinically to facilitate clinical diagnosis and prevention [ 13 , 14 , 15 ]. The biomarkers of DM have been studied by metabolomics, which also involve the metabolites on Hcy metabolism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the accompanying best practice, the authors discuss the diagnosis and management of homocystinuria, with particular emphasis on inherited metabolic disorders affecting the cobalamin pathway 16. In table 1 of the best practice paper, the authors outline the causes of mild hyperhomocystinaemia (HHC) (15–40 µmol/L), moderate (41–100 µmol/L) and severe (>100 µmol/L) 10 16.…”
mentioning
confidence: 99%
“…In the accompanying best practice, the authors discuss the diagnosis and management of homocystinuria, with particular emphasis on inherited metabolic disorders affecting the cobalamin pathway 16. In table 1 of the best practice paper, the authors outline the causes of mild hyperhomocystinaemia (HHC) (15–40 µmol/L), moderate (41–100 µmol/L) and severe (>100 µmol/L) 10 16. The providence for these cut-offs is mainly derived for cohort, case–controls studies of various sizes and so the CIs on these will be broad, with some overlap, particularly where more than one factor is at play 17.…”
mentioning
confidence: 99%
See 2 more Smart Citations